Current Panorama of Galician Cutural Industries: Cultural Public Politics - González Suárez, Marta (Madrygal. Revista de Estudios Gallegos, 2015)
Based on a socio-political analysis perspective, this work is about the state before the autonomy of Galicia and the immediate evolution of Galician public politics once its autonomy was set up, with the aim of understanding the current situation of our culture. At the same time, it exposes in detail the current concept of cultural industries and it reviews the strategies developed by this sector in our autonomous region as a mechanism to guarantee the cultural projects’ viability and autonomy.
Keywords: Galician cultural industry; cultural public politics; current cultural context of Galicia; Galician cultural initiatives